Handbuch Sprache in Mathematik, Naturwissenschaften und Technik - Atayan, Vahram; Metten, Thomas; Schmidt, Vasco Alexander (Handbücher Sprachwissen, 2023)
There are numerous individual studies available on the use of language in science, engineering, and mathematics. This handbook orders the field from a decidedly linguistic perspective by looking at the role played by language in the constitution and transfer of knowledge. This approach allows readers to learn more about the relationship between language and knowledge in these disciplines and provides starting points for future research